SAT0356 THE ROLE OF IL-36 AS A POTENTIAL NOVEL THERAPEUTIC TARGET IN SPONDYLARTHROPATHY ASSOCIATED PATHOLOGY DUE TO ITS UPSTREAM INDUCTION OF IL-23/IL-17 PATHWAY CYTOKINES AND STROMAL ACTIVATION IN AN IN VITRO ENTHESITIS MODEL. (2nd June 2020) - Sharif, K.; Bridgewood, C.; Russell, T.; Rowe, H.; Zhou, Q.; Rao, A. S.; Khan, A.; Dunsmuir, R.; Mcgonagle, D.
Abstract : Background: Enthesitis, defined as inflammation of anchorage points of tendons, ligaments and joint capsules to bones, is now understood to be the cardinal pathogenic lesion in spondyloarhtopathies (SpA). Evidence from genetic studies, animal models, and therapeutic studies firmly implicates the IL-23/IL-17 axis in the pathogenesis of SpA. We have recently confirmed the presence of IL-23 myeloid cells and IL-17 producing T cells populations in the human enthesis (McGonagle, ARD 2019). The upstream drivers of these key cytokines in the enthesis is, however, not defined. Emerging evidence suggests that IL-36 may be critical in regulating the IL-23/IL-17 axis in various organs. Also IL-38 SNPs have been associated with SpA which is of interest given that IL-38 is an IL-36 antagonist. Further, IL-36α is upregulated in the joints of psoriatic arthritis patients and deficiency of the IL-36 receptor antagonist (DITRA) results in generalized pustular psoriasis with comorbid arthritis in at least third of patients. Thus, we hypothesised that IL-36 could be an upstream regulator of the IL23/17 axis at the enthesis. Objectives: To confirm the induction of IL-36 at the human enthesis and to test the effect of IL-36 on resident innate and adaptive immune cell populations and enthesis stromal cells. Methods: Entheseal spinous processes from patients undergoing elective orthopaedic surgeries was obtained and mechanically digested. Peri-entheseal bone (PEB), and entheseal soft tissue (EST) digests were stimulated with fungal and bacterial adjuvants and IL-36 measured by ELISA. Disease relevant compounds such as methotrexate and PDE4i were assessed for their ability to attenuate IL-36 secretion. IHC was used to confirm the presence of IL-36R+ cells in the enthesis. Digested PEB was stimulated with IL-36, and IL-6, IL-8, IL-23, and TNF-alpha were analysed by ELISA and Flow Cytometry. As the IL-36 cytokines require protease mediated post translational processing for full activation, these were measured in enthesis digests. Entheseal fibroblasts were isolated and stimulated with IL-36 and ICAM-1 measured by Flow Cytometry and genes by qPCR. Results: TLR ligands induced the production of IL-36 at the enthesis. Further cell sorting, revealed CD11+ myeloid cells were the predominant entheseal producer of IL-36. Induced IL-36 could be significantly attenuated by PDE4i but not by methotrexate. IHC confirmed the presence of IL-36R+ in the enthesis. Stimulation of enthesis digest with IL-36 significantly upregulated the production of IL-6, IL-8, TNF-a, and IL-23. Stimulation of enthesis fibroblasts with IL-36 upregulated surface ICAM-1 and secretion of IL-6, CCL2 and CCL20. Enthesis digests showed high basal expression of IL-36 activating protease including cathepsin S and G. Conclusion: IL-36 is inducible from enthesis myeloid cells and IL-36R+ cells are present at the enthesis. Enthesis stimulation with IL-36 results in the upregulation of several disease relevant mediators such as TNF, IL-23 and CCL20 in both immune and stromal lineage cells. This is the first demonstration of IL-36 production in human enthesis. Given its pleiotropic effect and relation to IL-23/IL-17 axis, IL-36 is a potential novel therapeutic target in SpA. Disclosure of Interests: Kassem Sharif: None declared, Charlie Bridgewood: None declared, Tobias Russell Grant/research support from: Novartis UK Investigator Initiated non-clinical research funding support, Hannah Rowe Grant/research support from: Novartis UK Investigator Initiated non-clinical research funding support, Qaio Zhou: None declared, Abhay S Rao: None declared, Almas Khan: None declared, Robert Dunsmuir: None declared, Dennis McGonagle Grant/research support from: Janssen Research & Development, LLC